VOCABULARY AND SPEAKING ACHIVEMENT: A CORRELATIONAL STUDY AT ONE ISLAMIC BOARDING SCHOOL IN JAMBI - Putri, Tia Ratna; Amalia, Shynta; Ramdhani, Muhammad Iqbal (Borneo Journal of English Language Education, 2021)
The objective of the study was to find out whether or not there is any significant correlation between students’ vocabulary mastery and their speaking achievement. The study was correlational study. All of female students of the eight grade students at AL-Hidayah Modern Islamic Boarding School Kota Jambi were the population with the total number 163 students. The writer used purposive sampling to select the sample of the study. There were 30 students selected by means of several considerations; (1) The students were those who lived in dormitory, (2) The students’ speaking score taken from the school document were 80, (3) The students were those who were selected in the language program, (4) The students were those who did not take English course elsewhere. The data were collected by using two instruments; vocabulary and speaking tests. The data showed that most of students were categorized Excellent in their vocabulary achievement and good at their speaking achievement. The results of statistical data indicate that there was a positive correlation between vocabulary mastery and students’ speaking achievement. However the two variables were not significantly correlated [r=0.079, n=30, p0.05].  Keywords: Correlation, Vocabulary Mastery, Speaking Achievement